A Comparative Study on Maguindanaon Traditional Marriage and Islamic Marriage System. Issue 7 (2021) - Butuan, Omar S.; Abellar, Elisa M.; Mayasa, Samsiya D.; Blah, Sadat G.; Fiesta, Margie D.; Kasim, Osmeňa M.
No abstract available